Space weathering induced via microparticle impacts: 1. modeling of impact velocities and flux of micrometeoroids from cometary, asteroidal, and interstellar origin in the main asteroid belt and the near-earth environment - Altobelli, Nicolas; Fiege, Katherina; Guglielmino, Massimo; Trieloff, Mario (Journal of geophysical research. Planets, 2019)
Abstract The processes of alteration of airless bodies exposed to the space environment are referred to be as ?space weathering.? Multiple agents contribute generally to space weathering, to an extent that depends on the specific location of the surface within the solar system. Typical space weathering agents encountered in the solar system are solar radiation, solar wind and cosmic rays, magnetospheric plasma (e.g., at Jupiter or Saturn), and cosmic dust. The effect of space weathering is generally assessed by measuring the surfaces optical properties, for example, by near-infrared spectroscopy. The alteration of the surfaces is due to a cumulative effect over time of all agents. We investigate in this paper the contribution of micrometeoroid (dust) bombardment on different asteroids, by using the Interplanetary Micrometeoroid Environment Model for the interplanetary dust populations and a simplified model of interstellar dust dynamics. We quantify, for different representative asteroids (main belt and Near Earth Objects [NEOs]), the particle cumulative flux, mass flux, impact velocity, and the kinetic impact energy deposited. This work is primarily intended to support laboratory work investigating the effect of energy deposition onto sample surfaces, as well as astronomical observations of optical properties of asteroid surfaces.